Hubungan Peran Perawat Dalam Asuhan Keperawatan Dengan Fungsi Kognitif Pasien Pasca Stroke di RSUD Bogor: The Relationship Between the Role of Nurses in Nursing Care and the Cognitive Function of Post-Stroke Patients at Bogor Regional Hospital - Jabida Loukaki; Agus Purnama; Sancka Stella (Journal of Nursing Education and Practice, 2026)
Introduction: Stroke is a neurological condition that can cause significant cognitive impairment, affecting memory, attention, executive function, and language. Nurses play a central role in providing care and supporting cognitive recovery in post-stroke patients.Objectives: This study aimed to examine the relationship between the role of nurses and the cognitive function of post-stroke patients at RSUD Bogor.Methods: A descriptive correlational study with a cross-sectional design was conducted on 55 post-stroke patients with cognitive impairment. Data were collected using the Mini-Mental State Examination (MMSE) for cognitive function and a nurse role questionnaire assessing care provider, educator, and counselor functions. Data were analyzed using Chi-square tests with a significance level of 0.05.Results: The study found that 61.8% of nurses demonstrated poor role performance, while 38.2% had good role performance. Among patients, 49.1% experienced cognitive impairment. Chi-square analysis showed a significant relationship between the role of nurses and patient cognitive function (p = 0.020; OR = 4.583), indicating that better nurse role performance was associated with improved cognitive function.Conclusion: The role of nurses significantly influences the cognitive function of post-stroke patients. Effective nursing interventions, especially as educators and counselors, can enhance patient cognitive outcomes and support recovery.